Role of TNF-α in Renal Damage in Mice Showing Hepatic Steatosis Induced by High Fat Diet - Lai, Y. H.; Chen, L. J.; Cheng, J. T. (Hormone and Metabolic Research, 2013)
The present study was designed to investigate the role of TNF-α in renal damage observed in mice with hepatic steatosis. We induced hepatic steatosis in mice using high fat diet and treated mice with ectanercept at the dose sufficient to block TNF-α receptors or vehicle for 1 month. Plasma TNF-α, total cholesterol (TC), triglyceride (TG), LDL-cholesterol (LDL-C), and HDL-cholesterol (HDL-C) were determined at the end of this treatment. Renal damage was identified by histologic observation and the higher of serum blood urea nitrogen (BUN) and creatinine. Also, changes of PPAR-δ in kidney and renal mesangial cell (RMC) were analyzed using Western blot. Plasma TNF-α was markedly raised in mice showing hepatic steatosis. However, the levels of blood lipids (TC, TG, HDL-C, and LDL-C) and TNF-α were not modified by the treatment of etanercept although the hepatic steatosis has been improved. Etanercept shows renal protection from histological identification and recovery of serum BUN and creatinine levels. Moreover, restoration of PPAR-δ expression by etanercept was observed in mice kidney. Direct effect of TNF-α on PPAR-δ expression was also characterized in RMC cell. We suggest that renal damage in mice with hepatic steatosis is mainly induced by increase of TNF-α through the decrease of renal PPAR-δ. Etanercept could block TNF-α receptors to restore PPAR-δ and improve renal function in mice with hepatic steatosis.
Keywords: etanercept; hepatic steatosis; PPAR-δ; renal damage; TNF-α